Taxonomic and Ecological Assessment of Labeo rohita in the Kali River System: Insights from Uttarakhand, India - Sharma, Priyanka; Upadhyay, Lata; Verma, Rakesh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
In India, Uttarakhand is rich in its ichthyofaunal diversity, but in the Kali River system which is the largest in the Kumaun Himalaya, Labeo rohita has not been reported yet. This study investigates the taxonomy, morpho-biology, and habitat ecology of Labeo rohita. Taxonomic identification was conducted using diagnostic keys, fin formulae, and detailed descriptions, while morpho-biological analysis included 12 morphometric measurements, 6 meristic counts, and length-length relationships. Habitat ecology was assessed through 9 physicochemical parameters. The specimen was identified as Labeo rohita with negative allometric growth, supported by significant correlations between morphometric traits and physicochemical conditions which indicates healthy development. This first record of Labeo rohita in the Kali River system provides valuable insights into its taxonomy, growth, and ecological adaptations, contributing to the understanding and conservation of aquatic biodiversity in the Kumaun Himalaya.